2016
DOI: 10.1007/s00384-016-2734-z
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-associated lymphoid tissue (MALT) variant of primary rectal lymphoma: a review of the English literature

Abstract: Complete regression of primary rectal MALT lymphoma was achieved using various therapeutic strategies, although the numbers of different treatment modalities are too small to draw definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Approximately 20% of patients with colorectal MALT lymphoma are H. pylori positive, and other chronic inflammation has not been documented except for a case of rectal MALT lymphoma that was possibly associated with primary biliary cirrhosis and secondary Sjögren syndrome [ 37 , 38 , 39 ]. MALT lymphoma of the large intestine affects individuals in their fifth through seventh decades, with a female predominance [ 38 , 40 , 41 ]. The ileocecum and the rectum are commonly affected [ 40 , 42 ].…”
Section: Clinicopathological Features Of Gi Lymphomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 20% of patients with colorectal MALT lymphoma are H. pylori positive, and other chronic inflammation has not been documented except for a case of rectal MALT lymphoma that was possibly associated with primary biliary cirrhosis and secondary Sjögren syndrome [ 37 , 38 , 39 ]. MALT lymphoma of the large intestine affects individuals in their fifth through seventh decades, with a female predominance [ 38 , 40 , 41 ]. The ileocecum and the rectum are commonly affected [ 40 , 42 ].…”
Section: Clinicopathological Features Of Gi Lymphomasmentioning
confidence: 99%
“…Patients with colorectal MALT lymphoma sometimes present with abdominal discomfort, diarrhea, constipation, or a positive fecal occult blood test [ 40 , 43 ]. Approximately 90% of colorectal MALT lymphomas are localized clinical stage Lugano I-II, and bone marrow involvement is rarely seen (4–9%) [ 37 , 40 , 41 ].…”
Section: Clinicopathological Features Of Gi Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuo et al [ 13 ] reported a case of H. pylori -positive colon MALT lymphoma but did not report H. pylori eradication treatment. Kelley[ 14 ] retrospectively analyzed 51 primary rectal lymphoma patients, only 12 of whom were H. pylori -positive, and did not confirm a relationship between this bacterium and the disease because there was no direct pathological evidence on rectal biopsy. Kikuchi et al [ 15 ] summarized the literature on antibiotic treatment in patients with H. pylori -negative primary colorectal lymphoma and found that it may be associated with other luminal microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although most often found in the stomach, 2.5% of MALT lymphomas are found in the colon [2]. In addition, since colonic MALT lymphomas are often detected in the invasion depth of mucosal and submucosal layers as relatively small tumors, they are extremely rarely found as a deeply invasive mass-forming tumor [3][4][5]. The association between gastric MALT lymphoma and chronic Helicobacter pylori (H. pylori) infection is evident, so the treatment of gastric MALT lymphomas is well established.…”
Section: Introductionmentioning
confidence: 99%